2011
DOI: 10.4067/s0717-97072011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Diluted Acid Pretreatment of Pinus Radiata for Bioethanol Production Using Immobilized Saccharomyces Cerevisiae Ir2-9 in a Simultaneous Saccharification and Fermentation Process

Abstract: The production of bioethanol from pretreated lignocellulosic materials requires the utilization of microorganisms adapted to ferment the materials in conditions were high consistency, temperatures and inhibitors concentrations were commonly found. The yeast immobilization in calcium alginate capsules has been reported to enhance the yeast protection and increase the efficiency in the fermentation process. In this work, it was investigated the use Saccharomyces cerevisiae immobilized in calcium alginate and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In equations 1 and 2, the linear terms for time and temperature have positive coefficients, meaning that the content of hemicellulose or hexoses increased with the increase of these variables until a maximum value. Statistical analysis showed that the pH of solution was not a variable that influenced directly in the process according to the statistical model, similar to that describe by Franco et al 20 . Temperature was the main determining factor for maximum extraction of hemicelluloses, continued to time of extraction.…”
Section: Yield and Chemical Composition Of Hemicellulosic Extractssupporting
confidence: 74%
“…In equations 1 and 2, the linear terms for time and temperature have positive coefficients, meaning that the content of hemicellulose or hexoses increased with the increase of these variables until a maximum value. Statistical analysis showed that the pH of solution was not a variable that influenced directly in the process according to the statistical model, similar to that describe by Franco et al 20 . Temperature was the main determining factor for maximum extraction of hemicelluloses, continued to time of extraction.…”
Section: Yield and Chemical Composition Of Hemicellulosic Extractssupporting
confidence: 74%
“…87 Transmission electron microscopy showed that the residuals left, after processing cellulosic biomass for bioethanol, include an important amount of cellulose nanocrystals 88 especially in a bioethanol production from simultaneous saccharification and fermentation. 89,90 A recent report on the viability of the residue from a bioethanol process as a simple and low-cost source of raw material for nanowhiskers and the possibility of adding value to the bioethanol process was published and showed that the residue from bioethanol process was found to be as high as 48%. 91 In a report related to the case for bioethanol cost reductions through generation of a co-product, Winter 88 hypothesized two assumptions: one assumed, for example, a 90:10 ratio of cellulo-oligomers to nanocrystals, that are important to use in ethanol production and nanocrystals for reinforcing particles in nanocomposites, respectively, and the second considered the values of $0.22/kg for the oligomers and $2.21/kg for the nanocrystals.…”
mentioning
confidence: 99%
“…The hypothesis tested in the current work is e Can pine cones from Pinus radiata be a renewable feedstock for fuel ethanol production? Wood of P. radiata is well studied for ethanol production (Reyes et al, 2013;Franco et al, 2011;Fissore et al, 2010;Monrroy et al, 2010;Munoz et al, 2007). Unlike wood chips, the pine cones are a waste and renewable resource from P. radiata plantation.…”
Section: Introductionmentioning
confidence: 98%